Pleuropericarditis Associated with Sulphasalazine in a Case of Rheumatoid Arthritis: A Drug-Induced Lupus-Like Syndrome - Özcan HIZ,; Elif GÜLCÜ,; Yasemin ÖZKAN,; İbrahim TEKEOĞLU,; Nesim ALADAĞ2, (Archives of Rheumatology, 2011)
Pericarditis, a life-threatening condition, can be seen in rheumatic diseases. It may occur secondary to rheumatic diseases or drugs used in the treatment. In this article, we present a case of 47-year-old female, who had joint complaints for 15 years and had treatment of methotrexate and corticosteroid for six years. In the last three months, after the addition of sulphasalazine to her treatment, she developed chest pain, palpitations, rash, fever, and pleuropericarditis and was subsequently diagnosed with systemic lupus erythematosus induced by sulfasalazine. When cardiac disease is seen in a patient with rheumatoid arthritis, medication should be discontinued immediately, and it should be kept in mind that cardiac involvement may be associated with drugs.